До характеристики ключових елементів професійної підготовки працівників Національної поліції України - Діденко, В. В.; Didenko, V. V. (Держава та регіони. Серія: Право. – 2023. – № 3 (81). – С. 405-410, 2023)
Виокремлено ключові елементи професійної підготовки працівників Національної поліції України, які по-різному проявляються на різних етапах їх службової кар’єри. Так, одні з них супроводжують весь професійний шлях працівника органів та підрозділів Національної поліції України, інші – мають додаткове значення та реалізуються за якихось конкретних умов. Елементи професійної підготовки поліцейських найбільш доцільно поділити на: 1) основні, які включають засоби, заходи та способи навчання, розвитку та виховання поліцейських, які, по-перше, присутні протягом всього процесу службової кар’єри або на її конкретних етапах, по-друге, прямо впливають на хід та результативність кар’єри: службова підготовка у ЗВО зі специфічними умовами навчання та первинна професійна підготовка поліцейських; 2) додаткові елементи, що реалізуються за певних умов, зокрема: підвищення кваліфікації у закладах вищої освіти із специфічними умовами навчання; післядипломна освіта; самоосвіта, тощо.

The relevance of the article lies in the fact that the professional training of the National Police of Ukraine is a complex and multifaceted process that consists of a large number of elements. However, it would be fair to note that the issue of the structure of professional training and the classification of its components has no logical solution today. The existing legally enshrined approach is quite correct, however, it lacks full support in the scientific field, which in turn necessitates the implementation of a complex theoretical study devoted to the specified problem. The purpose of the article is to characterize the key elements of professional training of employees of the National Police of Ukraine and their classification. The article, based on the analysis of the scientific views of scientists and the norms of the current legislation, singles out the key elements of the professional training of the National Police of Ukraine. It is summarized that the elements of professional training of police officers presented in the article are manifested in different ways at different stages of their service career. Yes, some of them accompany the entire professional path of an employee of the National Police of Ukraine, others have additional importance and are implemented under certain specific conditions. It was concluded that the elements of professional training of police officers are manifested in different ways at different stages of their service career. Yes, some of them accompany the entire professional path of an employee of the National Police of Ukraine, others have additional importance and are implemented under certain specific conditions. In the first case, we are talking about necessary training, which directly depends on the development and further career of a police officer, as well as the effectiveness of his current official tasks and functions. In the second - secondary education, which strengthens the general level of awareness, education, moral and psychological qualities, as well as other subjective characteristics of a police officer as a professional. It is most appropriate to divide the elements of professional training of police officers into: 1) the main ones, which include means, measures and methods of training, development and education of police officers, which, firstly, are present throughout the entire process of the official career or at its specific stages, and secondly , directly affect the progress and effectiveness of a career: official training in higher education institutions with specific training conditions and initial professional training of police officers; 2) additional elements implemented under certain conditions, in particular: advanced training in higher education institutions with specific study conditions; postgraduate education; selfeducation, etc.

Выделены ключевые элементы профессиональной подготовки работников Национальной полиции Украины, которые по-разному проявляются на разных этапах их служебной карьеры. Так, одни из них сопровождают весь профессиональный путь работника органов и подразделений Национальной полиции Украины, другие – имеют дополнительное значение и реализуются при каких-либо конкретных условиях.
Keywords: професійна підготовка; professional training; профессиональная подготовка; елементи професійної підготовки; elements of professional training; элементы профессиональной подготовки; Національна поліція України; National Police of Ukraine; Национальная полиция Украины; класифікація; classification; классификация; поліцейські; police officers; полицейские